New insights of metabolite abnormalities in the thalamus of rats with iminodiproprionitrile-induced tic disorders - Yu, Jingru; Yao, Xuan; Zhang, Xin; Hao, Juanjuan (Frontiers in Neuroscience, 2023)
Introduction This study aimed to investigate pathological changes in the “Glutamate (Glu)-γ-aminobutyric acid (GABA)” loop and apply widely targeted metabolomic analysis technology to comprehensively explore metabolite abnormalities/ in the thalamus of rats with tic disorders (TD). Methods Wistar rats were randomized into control, TD, and tiapride (Tia) groups. Iminodipropionitrile (IDPN) was used to induce TD in rats. The Tia group was administered tiapride. Neurotransmitter levels in the thalamus of rats in the three groups were measured using UPLC-3Q MS. And, the protein expression levels of Glu decarboxylase (GAD65/67) and GABA transporter protein (GAD-T) were measured using western blotting. The mRNA expression levels of these genes were evaluated using real-time polymerase chain reaction. Lastly, other metabolites in the thalamus were detected by widely targeted metabolomic analysis between TD and Control group rats. Results The Glu level, Glu/GABA ratio, and Asp level in the TD group were significantly higher (all p < 0.001) than those of the Control group, whereas the GABA and Gly levels were lower (p < 0.001 and p = 0.009, respectively). The Tia group exhibited a significant reduction in the Glu level (p = 0.001) compared with the TD group. The protein expression level of GAD67 in TD group was higher (p = 0.009) and the mRNA expression levels of GAD65, GAD67, and GAT-1 were lower (p < 0.05) than those of the Control group. The Tia group did not display any differences in GAD65, GAD67, or GAT-1 expression. Widely targeted metabolomic analysis revealed that 34 substances were abnornal between the TD and Control groups (9 upregulated and 25 downregulated). Neurosteroids (progesterone, corticosterone) exhibited distinct differences. Metabolite analysis using the Kyoto encyclopedia for genes and genomes indicated that the steroid hormone biosynthesis pathway may be involved in TD pathogenesis. Conclusion This study revealed metabolic abnormalities in the thalamus of rats with TD. The interaction between neurotransmitters and neurosteroid biosynthesis represents a new direction for future studies.